Prognostic significance of treatment‐induced pathologic necrosis in extremity and truncal soft tissue sarcoma after neoadjuvant chemoradiotherapy. Issue 23 (31st July 2014) - Mullen, John T.; Hornicek, Francis J.; Harmon, David C.; Raskin, Kevin A.; Chen, Yen‐Lin; Szymonifka, Jackie; Yeap, Beow Y.; Choy, Edwin; DeLaney, Thomas F.; Nielsen, G. Petur
Abstract : BACKGROUND: Histologic response to chemotherapy has been shown to be an independent prognostic factor in patients with osteosarcoma and Ewing sarcoma. However, in patients with soft tissue sarcoma (STS), the prognostic impact of histologic response to chemotherapy is less clear. In the current study, the authors sought to determine the prognostic significance of treatment‐induced pathologic necrosis in patients receiving neoadjuvant chemoradiotherapy for STS. METHODS: Between 1989 and 2011, a total of 113 patients with grade 2 or 3 (graded according to the National Cancer Institute grading system using 3 tiers) extremity or truncal STS were identified who received neoadjuvant interdigitated chemoradiotherapy according to protocol followed by surgery. The extent of tumor necrosis in the resected specimens was quantified and correlated with outcome. RESULTS: The median tumor necrosis rate was 90%, and 103 patients (91%) received all 3 cycles of planned neoadjuvant chemotherapy. The likelihood of achieving ≥95% necrosis was not related to the number of preoperative cycles of chemotherapy received but was found to be related to tumor histology (62% for malignant fibrous histiocytoma vs 0% for synovial sarcoma [ P <.001]; 56% for myxoid liposarcoma vs 0% for synovial sarcoma [ P  = .002]). At a median follow‐up of 6 years, there were no statistically significant differences noted in the 5‐year local control, disease‐specific survival, and overall survival rates for patients with ≥95% necrosis (50 patients; 44%) and <95% necrosis (63 patients; 56%), even when stratifying by histology. CONCLUSIONS: In a homogeneous population of patients with high‐grade extremity and truncal STS who were treated with neoadjuvant chemoradiotherapy, the extent of pathologic tumor necrosis did not correlate with outcome. Cancer 2014;120:3676–3682 . © 2014 American Cancer Society . Abstract : Although histologic response to chemotherapy has been shown to be an independent prognostic factor in patients with osteosarcoma and Ewing sarcoma, its prognostic impact among patients with soft tissue sarcoma is less clear. In a homogeneous population of patients with high‐grade extremity and truncal soft tissue sarcoma who were treated with neoadjuvant chemoradiotherapy, the extent of pathologic tumor necrosis did not appear to correlate with outcome.